P1308PHOSPHATE-LOWERING USING SUCROFERRIC OXYHYDROXIDE: CALCIFICATION PROPENSITY (T50) IN HEMODIALYSIS PATIENTS. POST-HOC ANALYSES OF A RANDOMIZED, CONTROLLED CLINICAL TRIAL. (6th June 2020) - Thiem, Ursula; Marculescu, Rodrig; Pasch, Andreas; Haller, Maria; Cejka, Daniel
Abstract: Background and Aims: Lowering serum phosphate with sucroferric oxyhydroxide (SO) therapy reduces calcification propensity (measured with the T50 test) in hemodialysis patients (Cejka et al. Abstract FR-PO149, ASN Kidney Week 2019). Intriguingly, we observed considerable inter-patient variability for changes in T50 in response to SO treatment, despite similar reductions in serum phosphate. Method: Post-hoc analysis of a randomized, controlled cross-over study investigating the effects of serum phosphate lowering using oral phosphate binder therapy with SO on calcification propensity (T50 ). Patients with changes of serum phosphate of approximately -0.5 mmol/l between phosphate binder wash-out and high dose (2000 mg/d) SO and were selected and classified as "responders" (showing profound changes in T50 ) and "non-responders" (showing very little change in T50 ). Data are shown as means ± SD. Results: "Responders" (N=4) and "non-responders" (N=4) showed similar degrees of lowering of serum phosphate with high-dose SO treatment (-0.47 ± 0.06 vs. -0.49 ± 0.01 mmol/l). "Responders" showed marked increases in T50 (+108 ± 26 min), but "non-responders" did not (+6 ± 24 min). When comparing other laboratory parameters during the wash-out phase between "responders" and "non-responders", no obvious difference in single parameters or pattern of laboratory parameters was apparent for ionized calcium (1.11 ± 0.1 vs. 1.01 ± 0.1 mmol/l), phosphate (1.76 ± 0.31 vs. 2.06 ± 0.47 mmol/l), T50 (285 ± 82 vs 271 ± 38 min), albumin (3.9 ± 0.2 vs. 4.1 ± 0.4 g/dl), magnesium (1.07 ± 0.17 vs. 0.98 ± 0.14 mmol/l), bicarbonate (22.0 ± 3.6 vs. 24.1 ± 3.0 mmol/l), iPTH (301 ± 156 vs. 463 ± 303 pg/dl) or iFGF23 (6903 ± 9480 vs. 1097 ± 927 pg/ml). Conclusion: Similar degrees of phosphate lowering do not lead to a similar improvements in T50. T50 "responders" versus "non-responders" cannot be identified using current standard laboratory parameters.